Reduced Shear Stress and Longer Blood Flow Time Occur in Both Severe Focal and Mild Diffuse LAD Lesions: Angiograms Alone Don’t Always Reveal Their True Impact on Blood Flow - Gianluca Rigatelli; Marco Zuin; Niva Mileva; Dobrin Vassilev; Giuseppe Marchese; Ervis Hiso; Andrea Bertolini; Claudio Bilato (Pathophysiology, 2025)
Background/Objectives: The similarities and differences from a rheological perspective between significant short focal and mild long coronary lesions warrant investigation to elucidate wall shear stress (WSS) angiographic discrepancies. Methods: Patients who underwent coronary computed tomography angiography (CCTA) between 1 January 2023 and 1 September 2024 were selected for computational fluid dynamics (CFD) analysis. The selection criteria included either a focal (≤20 mm) hemodynamically significant stenosis, defined as ≥75% lumen narrowing, or a long (30–40 mm) non-hemodynamically significant lesion showing ≤50% stenosis of the left anterior descending (LAD) artery. Patient-specific models were reconstructed from ECG-gated CCTA images. Wall shear stress (WSS, measured in Pascals) and residence time (RT) were evaluated for each patient. Results: The LAD arteries of 30 patients (mean age 54 years, 63.3% men) were evaluated: 16 with focal, hemodynamically significant coronary stenosis, while 14 with diffuse, long, non-hemodynamically significant coronary lesions. Both groups exhibited a lower mean WSS compared to the non-stenosed segment, with no significant difference in mean WSS between the two groups (p = 0.84). Conversely, both groups demonstrated a higher mean residence time (RT) compared to the non-stenosed segments (0.2 ± 0.06 vs. 0.60 ± 0.03, p < 0.001 and 0.2 ± 0.006 vs. 0.59 ± 0.02, p < 0.001, respectively), and no significant difference in mean RT (p = 0.82). Conclusions: Long, angiographically mild coronary stenoses show similar WSS and RT characteristics compared to short hemodynamically significant coronary stenosis.